A new method to test the fracture strength of endodontically-treated root dentin. Issue 5 (May 2021) - Xu, Haiping; Ye, Ning; Lin, Fei; Heo, Young Cheul; Fok, Alex S.L.
Highlights: A new method to measure the fracture strength of treated root dentin is presented. Root dentin discs are fractured with a tapered plunger through the canal. This method simplifies sample preparation while providing more clinically relevant results. This model can be used to test the effects of all intracanal agents on root dentin. Abstract: Objective: To develop a new method to test the fracture strength of endodontically-treated root dentin. Method: Bovine tooth roots were transversely cut into 2-mm thick sections and the root canals were enlarged with a taper of 0.06. An outer layer of resin composite was bonded to each section to make the root canal-to-outer radius ratio smaller than 1/3. The resulting discs were treated with irrigants at the inner surface and then fractured by inserting through the center a steel rod of the same taper attached to a universal test system. Fracture strength was calculated by using Lame's equations for thick-walled cylinders. Micro-indentation was performed to evaluate the depth of dentin affected by irrigation. Finite element analysis (FEA) was performed to verify the reasonableness of using resin composite to surround the dentin section as well as the analytical solution. Results: The fracture strength of endodontically-treated root dentin based on the analytical solution for a homogeneous section was 139.69 ± 32.59 MPa. However, FEA that took into account root canal softening caused by the irrigants showed that this was overestimated by about 33.5%. The corrected fracture strength of treated dentin was 114.58 ± 26.74 MPa. By incorporating the layer of affected dentin into the analytical solution, the difference in the fracture-causing stress between the analytical and numerical solutions dropped to around 9.5%. Significance: A relatively simple but clinically relevant method has been developed for measuring the fracture strength of endodontically-treated root dentin. The method could be applied to root dentin that is treated by conventional canal opening and irrigation.